AI Use And Academic Integrity In EFL Writing: Students’ Practices, Motivations, And Perceptions In A Pesantren-Based College - Ibnu Syarofi; Durratul Hikmah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of Artificial Intelligence (AI) has transformed students’ approaches to English as a Foreign Language (EFL) writing by providing assistance in language production, idea development, and text revision. However, the use of AI in academic writing also raises concerns about academic integrity, particularly in educational contexts where academic learning is closely connected with moral and religious values. This study explores students’ practices, motivations, and perceptions regarding AI use in EFL writing in a pesantren-based higher education context in Indonesia. A qualitative case study design was employed involving six undergraduate students from the English Education Department at Universitas Nurul Jadid. Participants were selected purposively based on their experience with AI-assisted writing. Data were collected through face-to-face semi-structured interviews in July 2026 and analyzed using thematic analysis following Braun and Clarke’s six-phase framework. The findings indicate three major patterns of AI use: language support, idea development, and text refinement. ChatGPT was the most frequently mentioned tool, followed by Grammarly, DeepL, Gemini, and QuillBot. Students’ motivations were primarily associated with time efficiency and academic pressure, while linguistic limitations, writing confidence, and the desire to improve writing quality also influenced their use. Regarding academic integrity, students generally viewed AI as acceptable when used as a supporting tool rather than as a substitute for their own thinking. Nevertheless, uncertainty remained concerning the boundary between assistance and replacement. Pesantren values such as shidq, amanah, and barakah contributed to students’ ethical reflection and created tension when intensive AI use conflicted with their understanding of academic honesty. The study suggests that responsible AI integration requires clear institutional guidelines, AI literacy education, process-oriented writing assessment, and the integration of pesantren values into academic integrity education.